Central and Eastern Europe : roads to growth: papers presented at a seminar held in Baden, Austria, April 15-18, 1991 - Winckler, Georg, 1943-; International Monetary Fund; Oesterreichische Nationalbank (Washington [D.C.] : International Monetary Fund ; [Vienna] : Austrian National Bank, 1992)
The experience of Central and Eastern European countries with moving from centrally planned to open-market economies is examined in this collection of papers given at an April 1991 seminar, moderated by Georg Winckler and organized by the IMF and the Austrian National Bank.
Constantine MichalopoulosJohn Odling-Smee -- Salvatore Zecchini -- List of Participants
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Europe, Central -- Economic policy -- Congresses; Europe, Eastern -- Economic policy -- 1989- -- Congresses; Europe, Eastern -- Economic policy -- Congresses; Europe centrale -- Politique économique -- Congrès.; Europe de l'Est -- Politique économique -- Congrès.; Europe de l'Est -- Politique économique -- 1989- -- Congrès.; BUSINESS & ECONOMICS -- Economic Conditions; BUSINESS & ECONOMICS -- Economic History; BUSINESS & ECONOMICS -- Economics -- Comparative; POLITICAL SCIENCE -- Economic Conditions; Economic policy; Central Europe; Eastern Europe; Wirtschaftspolitik; Kongress; Wirtschaftsreform; Osteuropa; Economische politiek; Wirtschaftspolitik; Mitteleuropa; Osteuropa; Since 1989; Osteuropa -- Wirtschaftspolitik -- Kongress -- Baden (Niederösterreich, 1991); Osteuropa -- Wirtschaftsreform -- Kongress -- Baden (Niederösterreich, 1991); Conference papers and proceedings